KONDISI STOK IKAN KARANG DI KAWASAN KONSERVASI PERAIRAN TWP GILI SULAT DAN GILI LAWANG, KABUPATEN LOMBOK TIMUR - Muslihuddin Aini; Junaidi Junaidi; Lalu Alfitram Mame Malik; Asyifa Dwi Imelda (Universitas Mataram, 2024)
The Gili Sulat and Gili Lawang Marine Recreation Park (TWP) has a significant diversity of reef fish, but fishing activities threaten its stock. This research aims to estimate the stock condition of reef fish using a length-based stock assessment approach and Spawning Potential Ratio (SPR) analysis. Data were collected from two fish landing sites throughout 2023, covering fish species, catch results, and fish length data. A CPUE (Catch Per Unit Effort) analysis was conducted to assess fishing efforts and catches, while SPR was used to evaluate the stock condition of the fish. The research results show that 151 species of reef fish were caught, with three dominant species: Naso thynnoides (35%), Acanthurus mata (33%), and Caesio caerulaurea (32%). The SPR values of these three species were above 30%, indicating relatively healthy stocks (Naso thynnoides 58%, Acanthurus mata 43%, Caesio caerulaurea 34%). However, the exploitation rate of Acanthurus mata indicates that this species is fully exploited (E=0.578), requiring strict management to prevent overfishing. In conclusion, most reef fish stocks are in good condition, but Acanthurus mata requires special attention. Fishing control and regular monitoring are recommended to maintain the sustainability of reef fish stocks in TWP Gili Sulat and Gili Lawang.